The Giving of Guava Leaves Boiled Water to Postpartum Perineal Wound Healing - Zuhana, Nina; Prafitri, Lia Dwi; Ersila, Wahyu (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2018)
Labor often results in a tearing of the birth canal, either primigravida or multigravida with a rigid perineum. Approximately 85% of women who give birth spontaneously vaginal have 32-33% perineal trauma due to episiotomy and 52% are spontaneous lacerations. Perineal trauma may occure perineal infection due to poorly maintained perineal hygiene. This can be prevented by treating injuries. The research aims to know the effect of guava boiled water (psidium guajava linn) on the duration of wound healing of the postpartum nurse’s perineum. This research uses quasi-experimental research method with posttes control group design. Population used all postpartum with perineal sew wound in Pekalongan district in 2017 with sampling technique non probability sampling type consecitive sampling. Data analysis using un-paired t test showed that there was influence of guava leaf decoction (Psidium Guajava Linn) on the duration of wound healing of postpartum nurse perineum with significance value p 0,000 (<0,05).